The impact of image on customer satisfaction and loyalty in healthcare industry: a comparison study between the public and private hospitals in Kelantan / Zainudin Awang and Zaihan Othman @ Usman - Awang, Zainudin; Othman @ Usman, Zaihan (2004)
The service industry has becoming uniformed over time. When the differences between service characteristics are very marginal, if any, corporate image may make the difference between the service providers. This research posits that there is a significant correlation exists between image dimensions and perceived service quality, customer satisfaction, and customer loyalty in healthcare industry. The study found significant difference between hospitals on certain image dimensions namely; advice, customer relationship driven, social responsibility, and cost. The differences in image positioning among hospitals has contributed to the differences in service quality gap, with the significant differences found in the expectation on two service quality dimensions namely; assurance and empathy. The differences in expectations, in turn, caused the significant differences in customer perception towards different service providers. The service quality dimensions which have significant differences are reliability, responsiveness, assurance, and empathy. The study proved that different image dimensions among hospitals contributed to the differences on all loyalty factors namely; positive words of mouth, switching barriers, and willingness to pay more. The study also found positive relationship exists among central variables in the study namely; image, customer expectation, customer perception, service quality, customer satisfaction, and customer loyalty. Finally, the researcher estimated a multiple regression equation for each of the five central variables (customer expectation, customer perception, service quality, customer satisfaction, and customer loyalty) by using the six image dimensions (customer contacts, advice, customer relationship driven, social responsibility, position in the market, and cost).